GE_GERICHTE P/595/2023 vom 13. Mai 2025 - GE Cour de justice (2025)
ORDONNANCE DE CLASSEMENT;CONTRAINTE(DROIT PÉNAL);VOIES DE FAIT;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);INJURE | CPP.319; CP.126; CP.144; CP.177; CP.181